Maria Stuarda - Donizetti, Gaetano,Bardari, Giuseppe,Tagliabue, Carlo,Pizzi, Pier Luigi,Schiller, Friedrich,Tagliablue, Carlo,Fogliani, Antonino,Antonacci, Anna Caterina,Devia, Mariella,Meli, Francesco,Casoni, Bruno (ArtHaus Musik, 2008)
Enth. ausserdem: Documentary
101 361
Keywords: DVD-Video; Feature films; Operas